Pengembangan Modul IPA Muatan Perubahan Energi Berbasis Pendekatan Contextual Teaching And Learning (CTL) pada Siswa Kelas III SD Negeri 117 Palembang - Wulandari, Anjelia; Ferdiansyah, M; Syaflin, Sylvia Lara (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2022)
This study aims to (1) produce a valid CTL approach-based energy change science module product for third grade elementary school students, (2) produce a practical energy change charge science module product based on a practical CTL approach for third grade elementary school students, (3 ) produces an effective science module for energy change based on the CTL approach for third grade elementary schoolstudents. Needs analysis in this study is that teachers and students still use teaching materials in the form of thematic printed books, even teachers still use the lecture method in linking learning materials related to contextual (reality) and in thematic printed books related to energy change materials that are too short and have little material. In addition, the pictures in the thematic books are less varied in relating them to contextual matters. This research and development uses the ADDIE model development procedure (analysis, design, development, implementation, and evaluation). The subjects of this study were students of class III-A SD Negeri 117 Palembang with a total of 24 students. The quality criteria for the science module on energy change can be seen from the validation results of material, language, and media experts. The results of module validity based on material expert validation are 94.% categorized as veryvalid, linguist validation is 78% valid, media validation results are 90% categorized as very valid, and 70% practitioner validation is categorized as very practical. Then the assessment of the Small Group student response questionnaire is 99% categorized as very good. Based on what has been described, the IPA module based on the Contextual Teaching and Learning (CTL) approach is very feasible to use.